Sonic-spray introduction of liquid samples to hand-held Ion mobility spectrometry analyzers. Issue 6 (26th January 2021) - Pevzner, Alexander; Feldheim, Gil; Zaltsman, Amalia; Elisha, Shmuel; Heleg-Shabtai, Vered; Ron, Izhar
Abstract : Sonic spray vaporization of liquid samples for introduction to hand-held ion mobility spectrometry vapor analyzers. Abstract : Sampling hazardous compounds in the form of solids and liquids is a growing need in the fields of homeland security and forensics. Chemical analysis of particles and droplets under field conditions is crucial for various tasks carried out by counter-terrorism and law enforcement units. The use of simple, small and low cost means to achieve this goal is constantly pursued. In this work, an approach for rapid, continuous generation of vapors from liquid samples using sonic spray (SS) as the sample introduction technique, followed by analysis using hand-held ion mobility spectrometry (IMS) vapor analyzers is presented. Transfer of analytes is demonstrated from liquid state to the gas phase at the inlet of an IMS detector using a sonic spray apparatus that consists of a nebulizer, spraying solution, a source of compressed gas and an unheated transfer line tube to the detector inlet nozzle. This technique does not require any electrical, radiative or thermal energy. Analysis of several narcotic substances including cocaine, methamphetamine and amphetamine, and of an explosive compound, TNT, is demonstrated, using two commercial devices as analyzers. Two sampling configurations are presented: direct sampling of liquid, either from a vial or a spill (SS-IMS) and extraction of a substance collected with a swab by dipping it in the spray solvent (ESS-IMS), being suitable for both drops and particles. Limits of detection of the presented method are comparable to those obtained with thermal desorption sample introduction of the commercial device. Time traces of the IMS signals show a continuous and stable signal with a short rise time. This sampling technique may offer competitive performance to that of common thermal desorption techniques, with the advantages of coupling to simpler, smaller and cheaper vapor detectors, optimized for field use, and of a continuous, pulseless sample or object interrogation.